Sulfamethoxazole Susceptibility of Mycobacterium tuberculosis Isolates from HIV-Infected Ugandan Adults with Tuberculosis Taking Trimethoprim-Sulfamethoxazole Prophylaxis - Ogwang, Sam; Good, Caryn E.; Okware, Brenda; Nsereko, Mary; Jacobs, Michael R.; Boom, W. Henry; Bark, Charles M. (Antimicrob Agents Chemother, 2015)
Alternative drugs are urgently needed to treat multidrug-resistant (MDR) tuberculosis (TB). Given the difficulties of new drug development, repurposing currently licensed antibiotics is practical and efficient. Trimethoprim-sulfamethoxazole (SXT) is a fixed-dose drug combination used worldwide as treatment and prophylaxis for multiple infections. Sulfamethoxazole (SMX) is in the sulfonamide class of antibiotics, which were explored as an anti-TB treatment in the mid-20th century with early studies showing potential value for the treatment of pulmonary and miliary TB (1–5). More recently, Forgacs et al. reported defervescence of a patient with pulmonary TB who was initially treated with SXT alone and also demonstrated in vitro susceptibility to SXT in 43 of 44 Mycobacterium tuberculosis isolates (6). These drug susceptibility results were independently confirmed in laboratory strains (7, 8) and in patient isolates demonstrating SMX to be the active agent with MICs within achievable serum levels (9, 10). In addition, Alsaad and colleagues reported the use of SXT as part of a combination regimen used to treat 10 patients with MDR-TB in the Netherlands (11). They also reported M. tuberculosis susceptibility to SXT in 17 of 18 patients with TB-HIV coinfection; however, only 1 was taking SXT prior to TB diagnosis (12). Given the development of drug resistance when active TB is treated with a single drug, there is concern for resistance to SMX among TBHIV- coinfected patients taking SXT prophylaxis. To address this concern, we performed drug susceptibility testing (DST) on M. tuberculosis isolates obtained from pretreatment sputum specimens of HIV-infected patients taking SXT prophylaxis at the time of diagnosis of active TB. Sputum isolates used for
Keywords: Sulfamethoxazole; Mycobacterium tuberculosis; HIV; Ugandan Adults; Trimethoprim-Sulfamethoxazole Prophylaxis